PERLINDUNGAN HUKUM TERHADAP KORBAN TRAFFICKING ANAK DAN PEREMPUAN - Dadang Abdullah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Trafficking is the illicit and clandestine movement of persons across national and international borders, largely from developing countries and some countries and some countries with economies in transition, with the end goal of forcing women and girl children into sexually or economically oppressive and exploitative situations for the profit of recruiters, traffickers, and crime syndicates, as well as other illegal activities related to trafficking, such as forced domestic Labour, false marriages, clandestine employment and false adoption.